The United States and the Russian Civil War : the Betty Miller Unterberger collection of documents - Unterberger, Betty Miller (Scholarly Resources, 2001)
Includes "documentary materials covering the period of the First World War and its aftermath, especially relating to the United States, revolutionary Russia, and the Russian Civil War, Allied efforts to reestablish an Eastern Front, United States and Allied policy toward the Bolsheviks and later Admiral Kolchak's government; Allied and United States intervention in Russia, the Czech-Bolshevik conflict, the Czechoslovak liberation movement in Austria-Hungary and abroad, the United States and Japan in Eastern Siberia and China. It includes documents on the collapse and breakup of the Austro-Hungarian empire, the efforts of the United States and the Allies to negotiate a separate peace with that empire, the United States and Allied policy toward Russian at the Paris Peace Conference, Allied rivalries over the Chinese Eastern Railway; and the development and the application of the Wilsonian concept of self-determination not only in relation to empire but also to revolution itself." -- Guide to the Scholarly Resources Microfilm Edition.